Transcriptome analysis of immune response in recombinant cell vaccine expressing OmpK vaccinated juvenile seabass (lates calcarifer) head kidney against vibrio harveyi infection - Silvaraj, Santha; Md Yasin, Ina Salwany; Abd Karim, Murni Marlina; Saad, Mohd Zamri (Elsevier, 2021)
Seabass (Lates calcarifer) are high value fish occupying a market niche, and is susceptible to infection by pathogenic bacteria such as Vibriosis. In this study the effect of intraperitoneal administration of recombinant outer membrane protein (OMP) of inactivated cells vaccine; r-OmpK on hematological parameters for monitoring fish health and histopathological examination of seabass were investigated. The results revealed that r-OmpK affect some hematological parameters positively in juvenile bass. The r-OmpK vaccinated seabass showed mild histological alterations in the vital organs (spleen, kidney and intestine) when compared to PBS control groups. Further we sought to understand the mechanisms of molecular immunity of L. calcarifer against V. harveyi infection. We carried out an extensive analysis of the transcriptome of L. calcarifer head kidney upon vaccination trial with r-OmpK recombinant cell vaccine and challenged with V. harveyi pathogenic strain VH1. Average reads of 92.74 million and 116.17 million were obtained from head kidney of juvenile L. calcarifer immunized with phosphate buffered saline (PBS) and r-OmpK (10 9 cfu/mL) recombinant cell vaccine, respectively. Also, the analysis revealed that a higher number of genes and pathways were regulated in response to infection with V. harveyi at 48 h post infection compared to the PBS controls. Based on the differential expressed genes (DEGs) around 0.31 % of total unigenes were differentially expressed between the two vaccinated groups. Protein-protein interaction analysis predicts glycolysis pathway, alanine, aspartate and glutamate metabolism pathway, pyruvate metabolism pathway, MAPK signaling pathway, metabolic pathways, insulin signaling pathway and focal adhesion pathway in head kidney of infected fish, which might be useful in understanding biological processes and further studies in the direction of pathways. We reported the novel immune-related signalling pathways, namely complement and coagulation cascades, chemokine signalling pathway, and toll-like receptor signalling pathway having great importance in immunity and anti-inflammation.